2021
DOI: 10.3390/ani11020382
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Animal Welfare and Farm Profitability in Cow-Calf Operations with Stochastic Partial Budgeting

Abstract: The societal demand for good farm animal welfare (FAW) has increased over time. Yet, very little is known about the economic consequences of improvements in FAW in cow–calf operations. This study investigates on-farm economic consequences of improved FAW measures in cow–calf operations. It uses a stochastic partial budgeting approach to examine the relationship between contribution margins and improvements in FAW in terms of increased space allowance for a typical Swedish cow-calf operation, as compared to cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…We employed a partial budgeting framework with stochastic elements. The applied framework is a powerful tool for analysing decision-making on the farm and economic effects, particularly in situations where there is lack of detailed empirical data (Ahmed et al, 2021). It allowed us to take into account different 'what if' scenarios in the profitability analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We employed a partial budgeting framework with stochastic elements. The applied framework is a powerful tool for analysing decision-making on the farm and economic effects, particularly in situations where there is lack of detailed empirical data (Ahmed et al, 2021). It allowed us to take into account different 'what if' scenarios in the profitability analysis.…”
Section: Discussionmentioning
confidence: 99%
“…the longer the bar), the greater the impact of that specific input on the output. For a given variable, a positive coefficient, with bar extending to the right, shows the variable has a positive impact on the output and that an increase in the variable will increase the output Ahmed et al . (2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Fernandes et al (2021) the cost of infrastructure changes and staff training can be significant; access to capital is important in improving farm animal welfare. Therefore, Ahmed et al (2021) farm animal welfare improvements can be costly for farms, and these costs should be considered while taking policy decisions regarding improvements in farm animal welfare standards. The cost of ESCAS is very important considering that the feedlot and exporter already have an agreement to apply the principles of animal welfare from the feedlot to the slaughterhouse.…”
Section: Escas Costmentioning
confidence: 99%
“…Several studies contribute to this debate and have found positive (e.g., Alvasen et al 2017; Henningsen et al 2018) as well as negative relationships (e.g., Ahmed et al 2021; Ahmed et al 2020) between FAW efforts and on-farm economic performance. Previous literature has used expert assessments (Jensen et al 2012), simulations (Alvasen et al 2017; Ahmed et al 2020; Ahmed et al 2021), and primary data from commercial farms (Lawson et al 2004; Barnes et al 2011; Stott et al 2012; Henningsen et al 2018) to estimate the relationship between FAW and economic performance. Several studies have used animal health indicators (outcome-based measures) to proxy observed FAW or FAW efforts undertaken at the farm (e.g., Lawson et al 2004; Barnes et al 2011), while Henningsen et al (2018) used compliance with FAW regulations as an indicator of FAW.…”
Section: Introductionmentioning
confidence: 99%